EDUKASI KESEHATAN KULIT PADA MASYARAKAT DI KECAMATAN GANDUS - Wilsya, Mayaranti; Agustin, Yeni; Khairunnisa; Wahyudi, Achmad (STIK SITI KHADIJAH, 2025)
Skin health should be prioritized to reduce the number of patients with skin problems such as acne, blackheads, and so on. Skin health may not be a top priority for economically disadvantaged communities. However, if skin health is not maintained, it can lead to various diseases that can actually trigger significant financial expenditures for the healing process. In addition to the diseases caused by skin problems, skin diseases can lead to decreased enthusiasm for activities and decreased self-confidence. Therefore, regular programs such as skin health care are necessary for underprivileged communities. The results obtained showed that public understanding before being given education was in the good category, namely 10 people (35.7%), while after being given education, there was an increase in public understanding, namely in the good category, namely 22 people (78.5%). Through educational activities, it is hoped that this will increase public understanding and change behavior in realizing a healthy family from an Islamic perspective.